2021
DOI: 10.1016/j.ejmp.2021.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Establishing paediatric diagnostic reference levels using reference curves – A feasibility study including conventional and CT examinations

Abstract: To derive Regional Diagnostic Reference Levels (RDRL) for paediatric conventional and CT examinations using weight-based DRL curves and compare the outcome with DRL derived using the weight groups. Methods: Data from 1722 examinations performed at 29 hospitals in four countries were included. DRL was derived for four conventional x-ray (chest, abdomen, pelvis, hips/joints) and two types of CT examinations (thorax, abdomen). DRL curves were derived using an exponential fit to the data using weight as an indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…The variation in combinations of views was more than expected, although previous surveys have indicated such differences in ankle radiography [16]. More recent studies have also revealed a difference in the numbers of views for the same body part and indication [17].…”
Section: Discussionmentioning
confidence: 84%
“…The variation in combinations of views was more than expected, although previous surveys have indicated such differences in ankle radiography [16]. More recent studies have also revealed a difference in the numbers of views for the same body part and indication [17].…”
Section: Discussionmentioning
confidence: 84%
“…This leads to an underestimation of the dose for average‐sized adults and paediatric by 40–70% 21 . To address this concern, conversion factors to acquire size‐specific dose estimates (SSDEs) for specific patients have been suggested 15,22 . The SSDE is introduced to set the CTDI vol to show the effect of sizes of the patients on the average radiation dose, particularly for overweight patients with larger sizes and paediatric patients with smaller sizes 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“… 21 To address this concern, conversion factors to acquire size‐specific dose estimates (SSDEs) for specific patients have been suggested. 15 , 22 The SSDE is introduced to set the CTDI vol to show the effect of sizes of the patients on the average radiation dose, particularly for overweight patients with larger sizes and paediatric patients with smaller sizes. 23 , 24 The approaches and recommendations of calculating the SSDE have been updated in a later report; 25 however, its accuracy in estimating individual organ dose has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…A major problem is the large variation in patient size in infants and children in the same age group. This partially explains the large variation in radiation dose, in addition to other individual, institutional and national factors, all contributing to large variations across patients, institutions and countries [ 11 17 ]. Further, there is little consistency in grouping of patients into age and weight groups [ 1 , 16 18 ].…”
Section: Introductionmentioning
confidence: 99%